2005
DOI: 10.1080/15732480500453532
|View full text |Cite
|
Sign up to set email alerts
|

Load testing and model simulations for a stone arch bridge

Abstract: Service and high level load tests on a typical single span stone arch bridge in the south of Ireland and an associated set of three-dimensional nonlinear numerical analyses are discussed in this paper. The three-dimensional finite element models, which were generated using a commercially available finite element package, include the arch fill and a frictionless contact interface between this fill and the spandrel walls modelled with a nonlinear smeared crack material model. While this modelling strategy has been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Based on this correlated analytical model, the authors provided guidance in the FE model development for such bridges-particularly in the selection of material properties and definition of abutment stiffness. In another stone arch bridge study (Fanning et al 2005), service and high load level tests were used to establish the suitability of the authors' nonlinear FE modeling procedure for the given loading conditions. These methods, based on in situ strain or deflection measurements, were successful when applied to masonry bridges, however, the methods are impractical for larger masonry structures such as masonry cathedrals, due to the difficulty in sufficiently loading the structure to achieve a detectable response.…”
Section: Static Methods Of Correlationmentioning
confidence: 99%
“…Based on this correlated analytical model, the authors provided guidance in the FE model development for such bridges-particularly in the selection of material properties and definition of abutment stiffness. In another stone arch bridge study (Fanning et al 2005), service and high load level tests were used to establish the suitability of the authors' nonlinear FE modeling procedure for the given loading conditions. These methods, based on in situ strain or deflection measurements, were successful when applied to masonry bridges, however, the methods are impractical for larger masonry structures such as masonry cathedrals, due to the difficulty in sufficiently loading the structure to achieve a detectable response.…”
Section: Static Methods Of Correlationmentioning
confidence: 99%
“…The method also allows for the inclusion of a limited tensile capacity in the masonry mortar continuum. Further discussion on the inclusion of tensile strength for the masonry mortar continuum and validation of the modelling assumptions against service load testing can be found in Fanning et al (2005) and Fanning and Boothby (2003). The effect of increasing the tensile capacity is to increase the range of moment and force combinations permissible, as shown in the strength envelopes determined from Boothby and Fanning (2004) in Figure 4 for a masonry arch with a compressive strength of 7?0 MPa, a ring thickness of 0?460 m and tensile capacities of 0 MPa and 5% of the compressive strength; that is, 0?35 MPa.…”
Section: Elastic Methodsmentioning
confidence: 99%
“…Consistent with the 2D approach the fill is again only included as a dead load and the spandrel walls are not included. The exclusion of the spandrel walls is considered to be prudent as it has been shown that spandrel wall separation may occur without any visual evidence at the barrel spandrel wall interface (Fanning et al, 2005). Again, a single modulus of elasticity is taken for the masonry mortar continuum, the live loads are assumed to be distributed laterally over a 3 m width and in the longitudinal direction at a ratio of 1:2, and the masonry arch is assigned a compressive strength and, if appropriate, a limited tensile capacity.…”
Section: Three-dimensional Elastic Analysismentioning
confidence: 99%
“…A Bayesian approach was also used. Nonlinear 3D finite element (FE) models, including arch-fill interaction effects and limit analysis models, were also developed [10,[18][19][20][21][22][23][24]. The arch in masonry arch bridges was analyzed as a two-phase material comprising bricks (or stones) and mortar [13,25].…”
Section: Introductionmentioning
confidence: 99%